Consumer protection in the Slovak Republic - Jankalová, Miriam; Jankal, Radoslav (Business: Theory and Practice, 2009)
Consumer protection is one of the conditions of well – going economy. On the one hand it is covered by the state, on the other, it depends at full rate on the actions of enterpriser. Promoting consumers’ rights, prosperity and well being are core values of the European Union (EU), and this is reflected in its laws. Membership of the European Union ensures additional protection for consumers, what is described in 10 basic principles of how EU law protects you, as a consumer, no matter where you are in the EU. The protection of Slovak consumers extended to the protection of all European consumers. Article in German. Verbraucherschutz in der Slowakei Abstrakt. Verbraucherschutz ist eine aus den Anforderungen an die „gute“ Wirtschaft. Einerseits hängt von den Staat ab und anderseits erfordert er Engagement von Unternehmen. Die Förderung der Rechte und des Wohlergehens der Verbraucher gehört zu den Grundwerten der EU, was sich auch in ihrer Gesetzgebung widerspiegelt. Die Mitgliedschaft in der Europäischen Union bedeutet zusätzlichen Schutz für die Verbraucher, was 10 Grundsätze beschrieben werden, die Verbraucherinnen und Verbraucher in allen EU-Ländern gleichermaßen schützen. Der Schutz des slowakischen Verbrauchers hat sich über den Schutz aller europäischen Verbraucher verbreitet. Schlüsselwörter: Verbraucherschutz, Recht, Verbraucher, Qualität, Maßnahmen. First published online: 27 Mar 2009